Where in the cell is SIRT3?: Functional localization of an NAD(+)-dependent protein deacetylase - Hallows, William C. (2008)
Sirtuins are NAD(+)-dependent enzymes that have been implicated in a wide range of cellular processes, including pathways that affect diabetes, cancer, lifespan, and Parkinson’s disease. To understand their cellular function in these age-related diseases, identification of sirtuin targets and their subcellular localization is paramount. Sirtuin 3 (SIRT3) a human homologue of Sir2, has been genetically linked to lifespan in the elderly. However, the function and localization of this enzyme has been keenly debated. A number of reports have indicated that SIRT3, upon proteolytic cleavege in the mitochondria, is an active protein deacetylase against a number of mitochondrial targets. In stark contrast, some reports have suggested that full length SIRT3 exhibits nuclear localization and histone deacetylase activity. Recently, a report comparing SIRT3(−/−) and SIRT(+/+) mice have provided compelling evidence that endogenous SIRT3 is mitochondrial and appears to be responsible for the majority of protein deacetylation in this organelle. In the current issue of Biochemical Journal, Cooper et al. present additional results that address the mitochondrial and nuclear localization of SIRT3. Utilizing florescence microscopy and cellular fractionation studies, Cooper et al. determine that SIRT3 localizes to the mitochondria and is absent in the nucleus. Thus, this study provides additional evidence to establish SIRT3 as a proteolytically modified, mitochondrial deacetylase.